2014
DOI: 10.3945/ajcn.113.067199
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D supplementation increases calcium absorption without a threshold effect

Abstract: No evidence of a threshold of calcium absorption was found with a serum 25(OH)D range from 40 to 130 nmol/L. Calcium absorption in this range is not a useful biomarker to determine nutritional recommendations for vitamin D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 28 publications
0
47
1
1
Order By: Relevance
“…According to He aney and cols., individuals with 35 ng/mL of 25(OH)D presented higher absorption than those with 25 ng/mL (26) (B). Increase of calcium absorption with increasing dose of vitamin D 3 or serum 25(OH)D was recently ob served, but there is no evidence of what the minimum value of 25(OH)D to ensure calcium absorption from the intestine in the range of 1652 ng/mL evaluated in the study (27).…”
Section: What Are the Effects On Bone Metabolism?mentioning
confidence: 99%
“…According to He aney and cols., individuals with 35 ng/mL of 25(OH)D presented higher absorption than those with 25 ng/mL (26) (B). Increase of calcium absorption with increasing dose of vitamin D 3 or serum 25(OH)D was recently ob served, but there is no evidence of what the minimum value of 25(OH)D to ensure calcium absorption from the intestine in the range of 1652 ng/mL evaluated in the study (27).…”
Section: What Are the Effects On Bone Metabolism?mentioning
confidence: 99%
“…Active absorption is considered to be more important when dietary intake of calcium is limited. Multiple dual or single isotope studies carried out in adults and adolescents have examined the level of 25OHD at which intestinal calcium absorption is maximized or reaches a plateau, and have established that a plateau occurs below 20 nM 25OHD, with very little increase (if any) in intestinal calcium absorption above that value (7,24,26,306,650,774). Secondary hyperparathyroidism occurs at lower levels of 25OHD and maintains high levels of calcitriol despite the reduced availability of substrate, which may be why vitamin D deficiency does not impair intestinal calcium absorption until the 25OHD level is below 20 nM (650).…”
Section: Human Datamentioning
confidence: 99%
“…By contrast, a case‐control study by Zanardo et al (2014) of 25 overweight/obese and 25 nonoverweight/obese Italian mothers found women with higher BMI had more body dissatisfaction, yet were more likely to still be breastfeeding at six months postpartum. However, analysis of longitudinal data for 2824 women in the Infant Feeding Practices Study II showed overweight/obese women had similar intention to breastfeed as peers, but were less likely to initiate breastfeeding, and terminated breastfeeding sooner (Hauff, Leonard, & Rasmussen, 2014). …”
Section: Introductionmentioning
confidence: 99%